Between food studies and food semiotics: some methodological questions - Stano, Simona (E|C, 2020)
Being constitutively interdisciplinary, food studies encompass and combine various theoretical and methodological approaches. Although initially marginal, the semiotic reflection in such a field of research has progressively increased, developing in different directions. Building on these premises, this paper describes the main methodological tools and theoretical frameworks brought about by the study of the processes of meaning-making related to the food universe, also highlighting its major weaknesses and strengths.